A historical exploration on Church and State in Zimbabwe:the role of the Catholic Church for the Independence of Zimbabwe. - Chirongoma, Sophia (Harrassowitz Verlag, 2016)
The new nation of Zimbabwe was born on the night of 17 April 1980 with a 21-gun salute, a flaming torch, and a prayer. The leader of the Catholic Church in the country. Archbishop Patrick Chakaipa shared the dais at the independence ceremony with the newly elected Prime Minister, Robert Mugabe, the President, Reverend Canaan Banana, the Chief Justice, Mr. Hector McDonald and the guest of honour. Prince Charles. The morning after the celebrations, the Prime Minister, his wife Sally, and most cabinet members attended a special independence Mass at the Catholic Cathedral. The prominent role played by the Catholic Church during these celebrations was seen by many as a public acknowledgement of the support, which the Church had given to the nationalist guerrillas during the liberation war.1 While other Churches, such as the Evangelical Lutheran Church and the United Methodist Church, had also assisted the liberation movement, none had spoken out so publicly or as frequently as the Catholic Church nor suffered as many casualties, both at the hands of the guerrillas and the Rhodesian government’s security forces. Eighteen Catholic missionaries and one bishop had been deported. A bishop, 23 expatriate missionaries and one local priest had been killed. By March 1979, 65 Catholic mission stations, schools and hospitals had been closed. The Church’s Commission for Justice and Peace had been harassed and put on trial by the government, its officers arrested and deported, and its publications banned; most recently Mambo Press in Gweru had been blown up by government agents during the election campaign of 1980.This essay traces the role of the Catholic Church in the country's political struggles during the colonial era when Zimbabweans were fighting for independence. The Catholic Commission for Justice and Peace was founded in 1972 against the historical background of the Catholic Church’s teaching on justice and peace spelt out in various Papal encyclicals. The Commission’s motto was: If you want peace work, for justice.This article traces the Commission’s unrelenting, fearless and ceaseless quest for ensuring that “justice be done” from the time of the escalation of the Liberation War during lan Smith’s era, through to the early years of independence.’ It also analyses how, through its press statements and its publications on the infringement of human rights issues, the Commission strived to bring about a higher awareness in people of their socio-economic, civil, political and legal rights. It is also acknowledged that the Commission was very instrumental in facilitating the negotiations leading to the Commonwealth Conference held in Lusaka in May 1979, which led directly to the convening of the Lancaster House Conference, followed by the Lancaster House Agreement, a ceasefire and finally the democratic elections which led to Zimbabwe attaining its independence on I8 April 1980.